2017
DOI: 10.1098/rstb.2016.0390
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between photosynthetic electron transport and chloroplast sinks triggers protection and signalling important for plant productivity

Abstract: The photosynthetic light reactions provide energy that is consumed and stored in electron sinks, the products of photosynthesis. A balance between light reactions and electron consumption in the chloroplast is vital for plants, and is protected by several photosynthetic regulation mechanisms. Photosystem I (PSI) is particularly susceptible to photoinhibition when these factors become unbalanced, which can occur in low temperatures or in high light. In this study we used the pgr5 Arabidopsis mutant that lacks Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 67 publications
3
61
0
Order By: Relevance
“…First, CET supports proton influx to the lumen and low lumen pH is important for the engagement of NPQ. Hence, particularly, under conditions where linear electron transport is being limited, as was the case here with all three inhibitors, the engagement of NPQ is dependent upon CET (Munekage et al , Miyake et al , Nishikawa et al , Shikanai , Gollan et al ). While MYXO (and OLIGO) treatment greatly increased NPQ, this did not occur with AA (Fig.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…First, CET supports proton influx to the lumen and low lumen pH is important for the engagement of NPQ. Hence, particularly, under conditions where linear electron transport is being limited, as was the case here with all three inhibitors, the engagement of NPQ is dependent upon CET (Munekage et al , Miyake et al , Nishikawa et al , Shikanai , Gollan et al ). While MYXO (and OLIGO) treatment greatly increased NPQ, this did not occur with AA (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…E). Several previous studies have suggested the acceptor‐side limitation of PSI as a source of chloroplast retrograde signals (Piippo et al , Bräutigam et al , Foyer et al , Pfalz et al , Gollan et al , , Bode et al ).…”
Section: Discussionmentioning
confidence: 98%
“…It has been postulated that in PSI photoinhibition conditions, molecular oxygen functions as an electron acceptor from PSI, leading to the generation of reactive oxygen species (ROS), which can react with FeS centres at PSI and lead to the inhibition of electron transport activity (reviewed in Sonoike, ). PSI photoinhibition can occur at low temperatures (Havaux and Davaud, ; Terashima et al ., ; Tjus et al ., ), but can also occur under fluctuating light conditions (Suorsa et al ., ; Kono et al ., ; Tikkanen and Grebe, ) as well as under high light conditions (Tiwari et al ., ; Gollan et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Regularly occurring light variations induce long‐term acclimatory changes in the photosynthetic machinery via signaling mechanisms, while temporary fluctuation of light within a day transiently activates short‐term regulatory mechanisms (Armbruster et al., ; Bailey, Walters, Jansson, & Horton, ; Grieco, Tikkanen, Paakkarinen, Kangasjärvi, & Aro, ; Kono & Terashima, ). The short‐term mechanisms include nonphotochemical quenching (NPQ), photosynthetic control of electron flow between PSII and PSI, state transitions (ST), cyclic electron flow (CEF), and activation of photosynthetic enzymes both in light and carbon fixation (CBC) reactions (Balsera, Uberegui, Schürmann, & Buchanan, ; Demmig‐Adams, Cohu, Muller, & Adams, ; Gollan, Lima‐Melo, Tiwari, Tikkanen, & Aro, ; Tikkanen & Aro, ; Yamori, Makino, & Shikanai, ).…”
Section: Introductionmentioning
confidence: 99%